1986
DOI: 10.1620/tjem.148.57
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of plasma lipoproteins in survivors of cerebral infarction.

Abstract: To characterize the plasma lipoproteins in survivors of cerebral infarction, plasma lipoproteins were ultracentrifugally fractionated into VLDL, LDL, HDLZ and HDL3, and the concentrations of cholesterol, phospholipid, apolipoprotein and triglyceride in each lipoprotein class were determined. Subjects examined were 15 male healthy controls and 15 male survivors of cerebral infarction situated in the distribution of cerebral cortical artery. The concentrations of VLDL-cholesterol and VLDL-triglyceride and the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…It has been reported that VLDL-C is significantly associated with the thickness of the intima media of the common carotid artery, which reflects the degree of arteriostenosis [21]. In case control studies, significantly higher levels of VLDL-C have also been found in stroke patients than in health controls [10,22]. In our study, the serum level of VLDL-C is significantly lower in the PD group than the other three groups.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…It has been reported that VLDL-C is significantly associated with the thickness of the intima media of the common carotid artery, which reflects the degree of arteriostenosis [21]. In case control studies, significantly higher levels of VLDL-C have also been found in stroke patients than in health controls [10,22]. In our study, the serum level of VLDL-C is significantly lower in the PD group than the other three groups.…”
Section: Discussionsupporting
confidence: 56%
“…It is known that high blood levels of lipoproteins such as very low density lipoprotein (VLDL) and low density lipoprotein (LDL) transport triglycerides and cholesterols to peripheral blood vessels and accelerate the development of atherosclerosis. It has been shown that total cholesterol (TC), triglyceride (TG), high density lipoprotein cholesterol (HDL-C), very low density lipoprotein cholesterol (VLDL-C), low density lipoprotein cholesterol (LDL-C), apolipoprotein A (apo A), apolipoprotein B (apo B) and other lipids are associated with stroke [710]. The modification of TG in PD patients has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The uptake of phospholipids differs among the HDL subfractions (Hunter et al 1980). Through many clinical reports, the level of HDL-pl is known to decrease with certain types of disease (Ide et al 1980 ;Ide 1981;Chapkin et al 1983 ;Lacour et al 1985;Wallentin and Sundin 1985 ;Hachem et al 1986 ;Kostner et al1986 ;Murai et al 1986). However, there is no knowledge of pathological states which may hinder transportation of phospholipids (Spector 1984).…”
Section: Hdl-pl Obtained By Precipitation and Hdl2+3-p1mentioning
confidence: 99%
“…HDL-phospholipids ; VHDLphospholipids ; albumin ; phospholipids ; HDL-cholesterol Many researchers have measured phospholipids (HDL) using precipitation methods (Ide et al 1980;Hachem et al 1986;Kostner et al in high density lipoproteins Chapkin et al 1983 ;Lacour 1986) and ultracentrifugal methods (Wallentin and Sundin 1985;Murai et al 1986). Some investigators emphasized the clinical meaning of HDL-phospholipids (HDL-pl) as a negative risk indicator of atherosclerotic disease (Kostner et al 1986).…”
mentioning
confidence: 99%